SOCIOCULTURAL TRADITION AND DIGITAL SOCIETY: TWO STRATEGIC LANDMARKS OF THE CHINESE FORESIGHT TECHNOLOGY - M. Yu. Zakharov (Вестник университета)
The article analyses the features of the formation and strategic guidelines of the Chinese foresight technology, its potential opportunities, the limits of its use in order to build the desired digital future and determine specific steps to achieve it effectively. To this end, the author considers the archetypal traces of the predictive activity of Ancient China, their interaction with modern predictive practice as an integral part of the design of the alleged digital image of the future. The paper determines theoretical and methodological foundations of modern Chinese foresight technology, initial basic methodological principles and technology of prospective step-by-step application of comprehensive foresight, including the method of scenario design. The article pays special attention to the understanding of modern China foresight projects, possibility of their implementation on the national basis and impact of foresight results on the Chinese model of development and change management at the transition stage to digital society.